Retaining Alpha: The Effect of Trade Size and Rebalancing Frequency on FX Strategy Returns - Michael Melvin; Wenqiang Pan; Petra Wikstrom (Center for Economic Studies and ifo Institute (CESifo), 2020)
The literature on currency investing that incorporates transaction costs uses costs relevant for small trade sizes. Using the entire order book of the major electronic brokerages for FX, we compute sweep-to-fill costs for trades of different sizes and illustrate the reduction in post-cost returns as trade size increases. Researchers should consider trade size and frequency to create realistic forecasts of post-tcost returns to gauge the capacity of a strategy. We show how incorporating tcosts in the construction of a portfolio improves performance for both high and low frequency strategies and retains a larger portion of the alpha.
Keywords: G15; F31; 330; transaction costs; FX microstructure; exchange rates; portfolio construction